Single blind randomised controlled trial of GAME (Goals ⿿ Activity ⿿ Motor Enrichment) in infants at high risk of cerebral palsy. (August 2016) - Morgan, Catherine; Novak, Iona; Dale, Russell C.; Guzzetta, Andrea; Badawi, Nadia
Highlights: ⿢ Infants at high risk of CP were accurately identified using the General Movements Assessment or MRI. ⿢ GAME intervention led to improved motor outcomes when compared to standard care. ⿢ GAME participants had higher cognition scores at 12 months of age. Abstract: Background: Cerebral palsy (CP) is caused by a lesion in the developing infant brain. Recent neuroplasticity literature suggests that intensive, task-specific intervention ought to commence early, during the critical period of neural development. Aims: To determine whether ⿿GAME⿿ (Goals ⿿ Activity ⿿ Motor Enrichment), a motor learning, environmental enrichment intervention, is effective for improving motor skills in infants at high risk of CP. Methods and procedures: Single blind randomised controlled trial of GAME versus standard care. Primary outcome was motor skills on the Peabody Developmental Motor Scales-2 (PDMS-2). Secondary outcomes included Canadian Occupational Performance Measure (COPM), Bayley Scales of Infant and Toddler Development (BSID-III) and Gross Motor Function Measure-66 (GMFM-66). Outcome assessors were masked to group allocation and data analyzed with multiple regression. Outcomes and results: All n = 30 infants enrolled received the assigned intervention until 16 weeks post enrolment. At 12 months of age, n = 26 completed assessments. Significant between group differences were found in raw scores on the PDMS-2 in favour of GAME (B = 20.71, 95%CI 1.66⿿39.76, p = 0. 03) and at 12 months on the total motor quotient (B = 8.29, 95%CI 0.13⿿16.45, p  = 0.05). Significant between group differences favored GAME participants at 12 months on the cognitive scale of the BSID-III and satisfaction scores on the COPM. Conclusion: GAME intervention resulted in advanced motor and cognitive outcomes when compared with standard care.